Three-dimensional echocardiography of the tricuspid valve - Jost, Zachary T.; Nooli, Nishank P.; Ali, Ahmed E.; Jaganathan, Vijayadithyan; Nanda, Navin C. (Frontiers in Cardiovascular Medicine, 2023)
Due to the proportionally high mortality rates associated with isolated tricuspid valve surgery, the invasive treatment of such pathology, historically, has been left largely unaddressed. Recently, there has been an appreciation for the mortality and morbidity of tricuspid valve disease, giving rise to the movement towards identifying less invasive, transcatheter approaches for treatment. Due to the technical complexity of these procedures along with the uniqueness and variability of tricuspid valve anatomy, a better appreciation of the tricuspid valve anatomy and pathology is required for pre-procedural planning. While two-dimensional echocardiography serves as the initial non-invasive modality for tricuspid valve evaluation, three-dimensional echocardiography provides a complete en face view of the tricuspid valve and surrounding structures, as well contributes further information regarding disease etiology and severity. In this review, we discuss the utility of three-dimensional echocardiography as a supplement to two-dimensional imaging to better assess tricuspid valve disease and anatomy to aide in future innovative therapies.